Metabolism features in the injured hemisphere after experimental traumatic brain injury and transplantation of fetal neural tissue - Baranenko, Boris; Tsymbaliuk, Vitaliy; Vasileva, Irina; Chopik, Nataliya (Ukrainian Neurosurgical Journal, 2015)
Objective — to determine the phospholipid and neurotransmitter composition of the left (injured) hemisphere cortex in rats in a month after traumatic brain injury (TBI), and impact of fetal neural tissue (FNT) transplantation on these indexes. Methods. Severe TBI was modeled in inbred male adult rats. Transplantation of 18-day-old embryos FNT was performed 2 hours after TBI. Indole- and catecholamines were detected by high performance liquid chromatography; GABA — by condensation with ortho-phthalaldehyde; phospholipid fractions — by thin layer chromatography; Bax gene expression — by polymerase chain reaction with reverse transcription. Results. It was found that severe TBI reduced mass of the injured hemisphere and content of dophamine neurotransmitters, norepinephrine, serotonin, redistribution of phospholipids fractions was noted, as well as increase of level of pro-apoptotic Bax gene in the injured hemisphere, indicating destructive processes in the remote period after TBI. FNT transplantation promoted normalization of most parameters investigated. Conclusions. FNT transplantation in experimental animals with severe TBI contributes to the normalization of neurotransmitter and phospholipid composition of the injured hemisphere.